COA Induced Rainfall-Streamflow Variability in Warren River: Case Study - Rehman, Saqib Ur (Journal of Science and Technology, 2013)
Previous studies have linked ongoing winter drought in Southwest Western Australia (SWWA) to changes in local, as well as large-area, sea-level pressure. This paper examine the linkages between changes in the Indian Ocean High and rainfall-streamflow in Warren river basin in Southwestern Australia. The highest mean central pressure (MCP) of Indian Ocean High Pressure (IOHP) associated with decreased wintertime rainfall-streamflow and lowest MCP of IOHP associated with increased wintertime rainfall-streamflow. It was also found that east-west shifts in the position of this subtropical Indian Ocean high significantly influence winter rainfall-streamflow in Warren river. (IOHP and IOHLN) explain 29% variability of stream flow while SOI explains only 19%.